Pengaruh Penambahan Serat Baja Terhadap Kuat Tekan Beton - Adrian, Riki; Rahmawati, Cut; Silviana, Mery (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Concrete is a construction material that is often used in various applications such as buildings, bridges and other infrastructure. Concrete compressive strength is one of the most important parameters for determining the structural strength of a building. And concrete compressive strength is a major concern in the construction industry. One of the common problems with concrete is the risk of cracking. Especially under dynamic loads or extreme temperature changes. Therefore, as time goes by, many innovations have been made in the development of concrete, one of which is by adding fiber to the concrete mixture. This research aims to find out what is the optimal percentage for adding hooked steel fibers to the concrete mixture. The research method includes making and testing concrete samples with different steel fiber content variations, namely 0.5%, 1%, 1.5% and 1.8% using FAS 0.4. Compressive strength testing is carried out after the concrete reaches the age of 28 days. The research results show that the most optimal addition of steel fiber in concrete is a percentage of 0.5% with an average compressive strength of 348.20 Kg/cm². This increase is caused by the ability of steel fibers to resist crack propagation and micro tensile stress. However, if the fiber content is too high, there is a decrease in workability which causes the compressive strength of the concrete to decrease.